An Evaluation of the English Translational Version in the Vietnamese Bilingual Math Textbook Set "Toán 5" - Nguyễn Thị Bảo Yến (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The study is aimed at making an evaluation of the English translational version in the Vietnamese bilingual Math textbook set “Toán 5” mainly through three aspects, namely lexical, syntactic and textual given based on theory of House (2015). Then the study suggests some implications for teaching and learning grade 5 Math as well as for the revision of Vietnamese-English translation.